Optimizing calcium additions for a strength–corrosion resistance balance in squeeze-cast Zn–Al–Cu–Mg alloys - THIYAGESAN G; SankaraRaman Sankaranarayanan; S.P. Kumaresh Babu (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
In this study, squeeze-cast Zn–Al–Cu–Mg alloys with varying Ca additions (0, 0.5, 1.0, and 1.5 wt.%) were investigated to evaluate the combined effects of microstructural evolution on mechanical and corrosion performance. Microstructural analysis showed a transition from coarse Zn-rich dendrites in the base alloy to a refined and uniform morphology with Ca additions up to 1.0 wt.%, followed by coarsening and increased porosity at 1.5 wt.% Ca due to excessive intermetallic formation. Mechanical testing indicated that the alloy with 1.0 wt.% Ca had the highest hardness (141 HV0.1) and tensile strength (359 MPa), attributed to grain refinement and dispersion strengthening, though with reduced ductility due to intermetallic brittleness. Electrochemical corrosion tests in 3.5 wt.% NaCl solution showed that the corrosion rate decreased from the base alloy to 1.0 wt.% Ca, confirming enhanced corrosion resistance due to microstructural refinement and protective film formation. However, excessive Ca addition (1.5 wt.%) increased the corrosion rate to 0.8109 mpy due to coarse intermetallics and porosity, which promoted localized attack. The results highlight that optimal Ca addition (1.0 wt.%) achieves a balance between strength, hardness, and corrosion resistance, making Ca-modified Zn–Al–Cu–Mg alloys promising candidates for structural and functional applications.